Management of documentation support for public informatization projects in the archival and library sectors - I. V. Bakum; I. V. Zakharova (Scientific Notes of Junior Academy of Sciences of Ukraine, 2026)
The article examines the theoretical and practical foundations of managing documentation support for public informatization projects in the archival and library sectors in the context of digital transformation of public administration. The relevance of the research is substantiated by the active implementation of electronic archives, digital repositories, automated library and information systems, and other components of the digital infrastructure of documentary and cultural heritage. It is established that the effectiveness of such projects depends not only on the technological capabilities of software and technical solutions but also on the quality of documentation support, which ensures the recording of management decisions, coordination of the actions of project participants, monitoring of project tasks, verification of achieved results, information security, and long-term preservation of digital resources. The study identifies the main problems of contemporary documentation support, including fragmented regulatory and methodological frameworks, the lack of unified forms of technical and reporting documentation, inconsistencies in procedures for document approval and acceptance of completed work, insufficient recording of management decisions, risks associated with information duplication and the use of outdated document versions, as well as incomplete documentation of data migration and digital preservation processes. The specific features of documentation support for archival and library informatization projects are revealed, particularly those related to the authenticity of digitized documents, appraisal of the value of electronic copies, documentation of data migration, development of electronic catalogues, retroconversion of library collections, and licensing of digital content. The necessity of applying process-based and risk-oriented approaches to documentation support management is substantiated. According to these approaches, documentation processes cover the entire life cycle of a public project, from initiation and planning to implementation, commissioning of digital systems, evaluation of project effectiveness, and subsequent maintenance. A model for unifying documentation processes is proposed, providing for the use of coordinated forms of technical, organizational, financial, and reporting documentation, standardization of metadata, end-to-end documentation of management decisions, and integration of electronic document management systems with project management platforms. A conceptual model for managing documentation support is developed, integrating regulatory and legal, organizational, informational, technological, human resources, control, and analytical functional blocks. It is demonstrated that its implementation will contribute to greater transparency and accountability in management, reduced administrative costs, mitigation of documentation-related and legal risks, improved interagency cooperation, and the development of a unified digital information environment for the archival and library sectors. The practical significance of the research results lies in their potential application by public authorities, archival institutions, and libraries in planning, implementing, and documenting digital transformation projects. Further research should focus on developing sector-specific standards for documentation support, standardized project documentation packages, and methodologies for evaluating the effectiveness of documentation processes.